Analysis of the Regulatory Requirements for the Smart Grid in Chile - Rodriguez-Garcia, A (IEEE Computer Society, 2017)
In this article are analyzed and discussed what should be the rules that must be applied in Chile to deploy the smart grid. It examines what kinds of standards can be applied in various systems of the mains: in the generation, transmission and distribution are the characteristics of the rules for the transmission of data. It analyzes the characteristics of the network of smart meters, and there are regulations that must be met. © 2003-2012 IEEE.